2017
DOI: 10.1515/cclm-2016-1054
|View full text |Cite
|
Sign up to set email alerts
|

A candidate liquid chromatography mass spectrometry reference method for the quantification of the cardiac marker 1-32 B-type natriuretic peptide

Abstract: Background: B-type natriuretic peptide (BNP) is a 32 amino acid cardiac hormone routinely measured by immunoassays to diagnose heart failure. While it is reported that immunoassay results can vary up to 45%, no attempt of standardization and/or harmonization through the development of certified reference materials (CRMs) or reference measurement procedures (RMPs) has yet been carried out. Methods: B-type natriuretic peptide primary calibrator was quantified traceably to the International System of Units (SI) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Quantification accuracy is usually dependent on the quality and uncertainty of internal and external standards. Torma et al [25] developed a method of SI-traceable quantification for reference material preparation. During this work, synthetic BNP was quantified at the amino acid and peptide levels, which were obtained from hydrolyzed by hydrochloric acid or enzymatically digested by trypsin.…”
Section: Ms Analytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantification accuracy is usually dependent on the quality and uncertainty of internal and external standards. Torma et al [25] developed a method of SI-traceable quantification for reference material preparation. During this work, synthetic BNP was quantified at the amino acid and peptide levels, which were obtained from hydrolyzed by hydrochloric acid or enzymatically digested by trypsin.…”
Section: Ms Analytical Methodsmentioning
confidence: 99%
“…LGC has published works related to the development of the BNP reference quantitative MS method [25]. Once a BNP 1-32 purity reference material is developed, it can provide a standard value for instrument calibration.…”
Section: Reference Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers in this issue of Clinical Chemistry and Laboratory Medicine emphasize the wide range of applications of MS based methods [23][24][25][26][27][28][29][30]. The review by El-Najjar et al [23] highlights the crucial role of TDM of antibiotics in cancer patients: immunoassays are not available for all the classes of these drugs due to the difficulty in β-lactams ring reactivity or degradation.…”
mentioning
confidence: 99%
“…The study by Spanaus et al [29] serves as an example of differences in immunoassay performances, thus stressing the importance of evaluating each specific assay: results obtained on comparing two automated immunoassays for the measurement of 1,25 dihydroxyvitamin D with LC-MS/MS demonstrated that one immunoassay is appropriate for clinical purposes in view of its high sensitivity, low imprecision, broad measurement range and agreement with LC-MS/MS. Torma et al [30] developed a cRMP for 1-32 BNP with the potential to support external quality assessment schemes and to establish the bias of immunoassays, in order to enhance harmonization between results.…”
mentioning
confidence: 99%